Penentuan Kurva Retensi Air Dengan Menggunakan Fractal Padatan Pori (Pore Solid Fractal pada Alfisol tanpa olah tanah - Wirosoedarmo, Ruslan (Jurnal Teknologi Pertanian, 2004)
The water retention in the soil is determined by distribution of soil particle measurement.  The growth of the plants are influenced by the soil characters such as the structure, strength of the soil it self, the soil resitance to water The retention of the water can be estimated exactly by using the distribution data of particle measurement. So far, the determination of the water retention curve used is by using pressure plate, which is set in any pF, so it needs longer time. Model of the water retention characteristic is based on fractal model of soil structure. Up to now, soil structure is difficult to be quantitative or on the other hand, it is stated in qualitative, but by using fractal theory of soil structure, it can be quantitative. Fractal approach to set the water retention characteristic is based on water structure named Pore Solid Fractal (PSF). The model shows water retention characteristic related on water structure parameter, which means not only use the distribution of soil solid measurement related with model scaling.Calculating results by using data of measurement class and cumulative mass are D fractal dimension value 2.555 ± 0.404. D value is defined as fractal mass dimension because it is based on the soil cumulative mass. D value attained in this model cannot be obtained model estimation explicitly can be drawn. Based on the estimation of D value, if it is used for water retention curve will be obtained that in D value = 2.71 there is compatibility between analysis result and the calculation in modeling. The limitation of  D value needs to be done in order to get exact value (appropriate with the original condition).  Keyword: water retention, pore solid fractal, alfisol, and  soil structure